Impact of metabolic syndrome and its components on kidney stone in aging Taiwanese males. (2nd July 2016) - Lee, Yung-Chin; Huang, Shu-Pin; Juan, Yung-Shun; Huang, Tsung-Yi; Liu, Chia-Chu
Abstract: Objectives : Metabolic syndrome (MtS) and kidney stone are two common aging diseases with male dominant. This is the first study regarding the potential impact of MtS and its components on kidney stone in aging Chinese population. Methods : A total of 694 males with a mean age of 55.6 years were enrolled. The definition of MtS was according to the modified criteria developed by the Bureau of Health Promotion in Taiwan. Subjects were classified as having a disease of kidney stones according to diagnosis by a physician with available medical records or evidence from ultrasonography judged by an investigator of urologist. Results : Using age-adjusted multivariate logistic regression analysis, our results showed that subjects with kidney stone had significantly higher prevalence of MtS ( p = 0.04, OR = 1.74, 95% CI: 1.0 1–3.00). The presence of MtS had significant correlation with kidney stone ( p = 0.01, OR = 1.83, 95% CI: 1.1 4–2.93), which were associated with the increment of MtS components ( p < 0.01). After adjusting for age and testosterone level, abnormal blood pressure (BP) was the most significantly independent component of MtS for kidney stone among the MtS components ( p < 0.01, OR = 2.81, 95% CI: 1.46–5.39). Conclusions : In aging Taiwanese males, the presence of MtS and its components are strongly associated with kidney stone. Abnormal BP is the most significant risk component of MtS for kidney stone.